Force microscopy for the investigation of high-frequency surface acoustic wave devices - Hesjedal, T; Frohlich, H; Chilla, E (1998)
Surface acoustic wave (SAW) devices are of great importance in mobile communication and signal processing applications. For their optimization second-order effects, like diffraction or mass loading, have to be studied. However, meeting today's demands of GHz operation new ways of wave field mapping have to be developed, since common methods, like laser optical or electron microscope probing, are resolution limited to the micron range. Scanning acoustic force microscopy (SAFM) allows the detection of the high-frequency surface oscillations having sub-Å amplitudes with the force microscope's typical lateral resolution. The key for measuring the high mechanical frequencies is the nonlinear force curve. Another approach is the force microscope mapping of rearranged fine particles, revealing the nodes and antinodes of the standing wave field. We present measurements in the near field of, and within, acoustic devices fabricated on piezoelectric substrates, such as LiNbO3 and quartz, and being operated at frequencies around 600MHz. By employing SAFM, the local influence of the electrodes on the wave field, leading to undesired performance losses, was investigated. © 1998 Springer-Verlag.